2012
DOI: 10.1007/s12094-012-0934-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of economic evaluations of pharmacological cancer treatments in Spain between 1990 and 2010

Abstract: Economic evaluation of pharmacological cancer treatment is a critical clinical problem currently under consideration worldwide. We have analysed their main characteristics in Spain between 1990 and 2010 following a systematic review of the 29 complete economic analyses published. The pathology most frequently evaluated was non-small cell lung cancer (31 %). Cost-effectiveness analyses (69 %) were the most frequent analyses. A wide range of incremental cost-effectiveness values (295-160,667 € /QALY) has been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Consistent with these findings, another review of 242 cancer-related CUAs published in different parts of the world, through 2007, showed that the most frequent cancers studied were breast cancer (36% of studies), colorectal cancer (12%), and hematologic cancers (10%) ( 70 , 71 ). In Spain, 13.0% of economic evaluations, published between 1990 and 2009, referred to cancer-related processes ( 72 ), and the disease most frequently evaluated was non-small cell lung cancer (31 %) ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, another review of 242 cancer-related CUAs published in different parts of the world, through 2007, showed that the most frequent cancers studied were breast cancer (36% of studies), colorectal cancer (12%), and hematologic cancers (10%) ( 70 , 71 ). In Spain, 13.0% of economic evaluations, published between 1990 and 2009, referred to cancer-related processes ( 72 ), and the disease most frequently evaluated was non-small cell lung cancer (31 %) ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The debates on methodological aspects and practical application of EE are similar to international ones [17][18][19] and with common emphasis on the need to improve the quality and credibility of EE. [20][21][22][23][24] This activity has been carried out by agents from both the public and private sectors. On the public side, the 8 HTA agencies in Spain have been coordinated through the Spanish Network of HTA Agencies (RedETS) since 2012.…”
Section: Development Of the Legal And Policy Framework For The Use Ofmentioning
confidence: 99%
“…En este ámbito, los de tipo coste-utilidad están adquiriendo cada día mayor relevancia al incorporar la dimensión de la calidad de vida, unida al hard endpoint más importante, la muerte. Así, en la actualidad se publican con frecuencia revisiones sistemáticas de las evaluaciones económicas efectuadas en una gran variedad de tratamientos, como cáncer de pulmón de células no pequeñas (35) , esquizofrenia (36) , Alzheimer (37) , tuberculosis resistente (38) , púrpura trombocitopénica (39) , o incluso, análisis de las evaluaciones económicas efectuadas en nuestro país, durante los últimos años, en campos más amplios como el cáncer (40) , las vacunas (41) o los trastornos mentales (42) .…”
Section: Eficiencia De Los Tratamientos Farmacológicosunclassified